Enhancing Performance Management System Through Gamification: A Comprehensive Review and Improvement - Bangkit Puri Nugroho; Emilia Fitriana Dewi (Lembaga Riset dan Inovasi Al-Matani, 2025)
Traditional Performance Management Systems (PMS) often face criticism for being rigid and demotivating. Gamification, the use of game design elements in non-game contexts, has emerged as an innovative approach to enhance PMSs by engaging and motivating employees. PT XTA's PMS faces challenges such as a lack of transparency, motivation, and engagement. Employees seek clarity on how performance assessments impact their career progression and remuneration. The current PMS lacks stimulating elements, leading to decreased motivation and participation. This research aims to review and improve the existing PMS at PT XTA by integrating gamification. The data was analyzed using qualitative techniques, including content analysis for interviews and interpretative observation for observations. The research concludes that while PT XTA's PMS has advantages like facilitating SMART goal setting and multi-source feedback, it faces significant challenges such as a lack of transparency and overly ambitious goals leading to employee stress. Gamification can address these challenges by enhancing transparency, motivation, engagement, and continuous learning. Recommendations for incorporating gamification into the PMS are proposed based on the findings.